Results of a Diagnostic Procedure Based on Multiplex Technology on Dried Blood Spots and Buccal Swabs for Subjects With Suspected Alpha1 Antitrypsin Deficiency - Lopez-Campos, Jose Luis; Casas-Maldonado, Francisco; Torres-Duran, Maria; Medina-Gonzálvez, Agustin; Rodriguez-Fidalgo, Maria Luisa; Carrascosa, Ines; Calle, Myriam; Osaba, Lourdes; Rapun, Noelia; Drobnic, Estrella; Miravitlles, Marc (Archivos de bronconeumología (English ed.), 2021)
[Display omitted] The objective of this analysis was the evaluation of a new national circuit used for diagnosing alpha1 antitrypsin deficiency (AATD) based on multiplex technology using online registration and mail posted samples from dried blood spots (DBS) and buccal swabs. This is an observational, ongoing study conducted in Spain since March 2018. Samples are coded on a web platform and sent by postal mail to the central laboratory. Allele-specific genotyping for the 14 most common mutations was done with the Luminex 200 Instrument System. Gene sequencing was done if none of the mutations were found and the AAT serum level was <60mg/dl, or by request from the clinician in charge. At the time of the present report, 5803 (92.9%) samples were processed, 4984 (85.9%) from buccal swab and 819 (14.1%) from DBS. The prevalence of the frequent allele combinations were: MS 19.0%, MZ 14.4%, SS 2.9%, SZ 3.7%, and ZZ: 1.4%. Globally, Z carriers represented 20.0% and S carriers 26.6% of this population, with differences seen between regions. 209 (3.6%) were identified carrying rare alleles, 12 (0.2%) carrying null alleles and 14 (0.3%) new mutations were described. Respiratory diseases other than COPD, including poorly controlled asthma or bronchiectasis, also presented AATD mutations. The availability of a diagnostic system based on the simultaneous testing of 14 genetic variants from buccal swabs or DBS sent by postal mail and with web registration has proven to be useful, and the system can improve the timely diagnosis of AATD. El objetivo de este análisis fue la evaluación de un nuevo circuito nacional utilizado para diagnosticar la deficiencia de alfa-1 antitripsina (DAAT) basado en tecnología multiplex con muestras de manchas de sangre seca (DBS, por sus siglas en inglés) y frotis bucales enviados por correo postal tras un registro previo en línea. Este es un estudio observacional en curso que se está llevando a cabo en España desde marzo de 2018. Las muestras se codifican en una plataforma web y se envían por correo postal al laboratorio central. El genotipado de un alelo específico buscando las 14 mutaciones más comunes se realizó con el sistema Luminex® 200. Se realizó secuenciación génica si no se encontraba ninguna de las mutaciones y el nivel sérico de AAT era <60mg/dl, o por solicitud del médico responsable. En el momento del presente informe se habían procesado 5.803 (92,9%) muestras, 4.984 (85,9%) de frotis bucal y 819 (14,1%) de DBS. La prevalencia de las combinaciones frecuentes de alelos fue: MS 19,0%, MZ 14,4%, SS 2,9%, SZ 3,7% y ZZ 1,4%. Globalmente, los portadores de Z representaron el 20,0% y los portadores de S el 26,6% de esta población, observándose diferencias entre las regiones. Se identificaron 209 (3,6%) portadores de alelos raros, 12 (0,2%) portadores de alelos nulos y se describieron 14 (0,3%) nuevas mutaciones. Otras enfermedades respiratorias que no eran EPOC, incluyendo el asma mal controlado o las bronquiectasias, también presentaron mutaciones DAAT. La disponibilidad de un sistema de diagnóstico con registro web basado en el análisis simultáneo de 14 variantes genéticas de frotis bucales o DBS enviados por correo postal ha demostrado ser útil, y el sistema puede mejorar el diagnóstico temprano de DAAT.